Developing Information Technology Competence in Online Education with the TPACK Approach (Journal of Contemporary Educational Policies and Practices, 2024)
The integration of technology in education has become imperative, particularly in the context of online learning. The TPACK (Technological Pedagogical Content Knowledge) framework provides a comprehensive approach to developing information technology competence among educators. This study explores the application of the TPACK framework in online education, focusing on its effectiveness in enhancing educators' abilities to integrate information technology with pedagogy and content knowledge. By analyzing case studies, surveying educators, and assessing online teaching outcomes, the research highlights the pivotal role of TPACK in fostering a holistic understanding of how technology can be seamlessly incorporated into educational practices. The findings suggest that educators equipped with TPACK are better prepared to design and deliver engaging, effective online learning experiences, ultimately leading to improved student outcomes. This study underscores the necessity for professional development programs that emphasize TPACK to ensure educators are proficient in utilizing technology in their teaching methodologies in higher education institutions. This aligns with the prevailing trend of online teaching during the Covid-19 pandemic.